Monocyte response after colorectal surgery: A prospective cohort study - Edomskis, Pim P.; Dik, Willem A.; Sparreboom, Cloë L.; Nagtzaam, Nicole M. A.; van Oudenaren, Adrie; Lambrichts, Daniël P. V.; Bayon, Yves; van Dongen, Noah N. N.; Menon, Anand G.; de Graaf, Eelco J. R.; Coene, Peter Paul L. O.; Lange, Johan F.; et al. (Frontiers in Immunology, 2022)
Background: Tumor resection is the common approach in patients with colorectal malignancy. Profound insight into inflammatory changes that accompany the normal post-operative stress response will establish reference parameters useful for identification of putative complications. Alterations in circulating monocytes might be indicative as these cells are considered to be the most responsive leukocytes to trauma. Therefore, the aim of this study is to assess the monocyte subset kinetic and phenotypic changes in response to surgery. Methods: Fifty patients undergoing colorectal tumor resection were included in a multicenter prospective cohort study. Blood samples were collected early in the morning prior to surgery and the next days through postoperative day three for flowcytometric analysis. Leukocyte subtypes were identified and expression of activation stage-related markers by monocyte subsets was quantified. Results: Changes in leukocyte subset composition and monocyte subset phenotypes were most prominent at the first day postoperatively, after which these parameters typically returned to normal or near-normal preoperative values. The immunophenotypic alterations after surgery were most notable in classical and intermediate monocytes. These included up-regulation of activation markers CD64 and CD62L, but down-regulation of HLA-DR and CD54. Markers of de-activation, CD163 and CD206, were consistently increasingly expressed. Discussion/Conclusion: The current study gives detailed insight into the peripheral blood leukocyte response after colorectal cancer surgery. This form of short-term stress induces a rapid and significant redistribution of immune cells. Immunophenotypic alterations in monocytes as a response to surgery suggest a mixed profile of cellular activation and de-activation.